ANALISIS PENERAPAN TARGET COSTING DALAM SISTEM PENGENDALIAN BIAYA PRODUKSI PADA TOKO ULUMUNA PAMEKASAN - Siti Salama Amar; Devi Lestari Pramita Putri (Masyrif : Jurnal Ekonomi, Bisnis dan Manajemen, 2022)
This study aims to determine the classification of production costs Petis Toko Ulumuna Pamekasan, to analyze the target costing approach in order to increase the cost efficiency of Petis production and to compare between standard costs and target costing. From the results of the analysis regarding the calculation of standard production costs in producing Petis, it appears that the standard production cost for Tuna Petis is Rp. 1,915,580 Based on the results of a comparative analysis of the application of target costing with the company's standard production costs regarding the implementation of target costing is much more efficient, whereby the application of target costing, with production prices as follows: Production costs for Tuna Petis Rp. 1,558,538.